2000
DOI: 10.1111/j.1151-2916.2000.tb01402.x
|View full text |Cite
|
Sign up to set email alerts
|

Lead Zirconate Titanate Particle Dispersion in Thick‐Film Ink Formulations

Abstract: Diverse device applications for lead zirconate titanate (PZT) ceramics in thick-film form are currently in active development. In the present study, the particle dispersion properties of thick-film ink formulations containing PZT powder have been determined using rheological measurements. Although all of the eight commercially available dispersants tested are more effective than the terpineol solvent alone in decreasing attractive interparticle forces in suspensions, the best dispersant identified for hard and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 23 publications
(21 reference statements)
1
14
0
Order By: Relevance
“…Although efforts have been made to link the interparticle forces with slurry formulation, it is often only treated qualitatively via zeta potential or viscosity measurements. 11 Although there are many limitations with computing interparticle forces and potentials (i.e. particle shape), knowledge based progress in ceramic processing cannot proceed without understanding the key factors determining the rheological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Although efforts have been made to link the interparticle forces with slurry formulation, it is often only treated qualitatively via zeta potential or viscosity measurements. 11 Although there are many limitations with computing interparticle forces and potentials (i.e. particle shape), knowledge based progress in ceramic processing cannot proceed without understanding the key factors determining the rheological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Since the organic additives decompose at much lower temperatures than that at which the 8YSZ particles sinter and in decomposing they produce big volumes of gas this has to be taken into consideration when designing the sintering program. Thiele and Setter found that PE compounds volatilize well below 900 8C [37]. A detailed description of the thermal decomposition processes for PVB can be found in the work of Masia et al [38].…”
Section: Dip-coating Of the Electrolyte Layersmentioning
confidence: 97%
“…Dispersants act to create repulsive forces between the particles, thus reducing clumping and increasing the homogeneity of the film. Thiele and Setter [7] have studied various dispersants and their effects on the rheology of thick-film pastes. Their experiments looked at eight commercially available dispersants with a Sensor Technology BM500 PZT powder.…”
Section: Formulationmentioning
confidence: 99%